A Straighter Kind of Hip∗. - Scott, Felicity D. (October)
This article recovers Resource One, an "alternative" computer-resource center founded in San Francisco in 1971 and celebrated by Whole Earth Catalog–founder Stewart Brand as a "counter-computer" initiative in his 1972 Rolling Stone article "Spacewar: Fanatic Life and Symbolic Death Among the Computer Bums." Departing from the usual mythologizing of personal computing often linked to Brand's rhetoric of "access to tools," this reading re-situates Resource One in the urban commune where it was located, Project One. Optic Nerve's video documentary about the communards' life there, Project One (1972), serves as both archive and interpretation of the commune, helping to demonstrate the economic and political utility of the ambivalence harbored within the notion of participation and the ethos of do-it-yourself. The essay ties the logic of participation to the emergence of a new topology of material and informatic domains as well as to novel configurations of home and work. It does so to trace forms of subjectivity that were then being forged through computerization in the service of a postindustrial economy.